2018
DOI: 10.5435/jaaos-d-17-00318
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Treatment Comparisons for Nonsurgical Treatment of Knee Osteoarthritis: A Network Meta-analysis

Abstract: Naproxen ranked most effective among conservative treatments of KOA and should be considered when treating pain and function because of its relative safety and low cost. The best available evidence was analyzed, but there were instances of inconsistency in the design and duration among articles, potentially affecting uniform data inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 65 publications
0
67
2
Order By: Relevance
“…We would like to highlight that despite the fact that in the last 15 years many randomized controlled trials and at least 40 meta-analyzes have been published on the effectiveness and safety of IAHA for the treatment of KOA, there is still much controversy and uncertainty on this topic. [ 31 ] If we consider only some of the meta-analyzes published in the past 5 years, we will see that some of them recommend IAHA as a very effective and safe treatment, [ 24 , 32 34 ] while others contraindicate this intervention, [ 31 , 35 , 36 ] both due to its low effectiveness, as well as the lack of safety. We can explain these conflicting results for several reasons: the low quality of the meta-analyzes, [ 31 ] individual differences in the formulation of the IAHA, [ 30 ] specific clinical characteristics of the patients [ 37 ] and even the presence of conflicts of interest (declared or not) by the authors of the studies and/or financing of studies by the industry.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to highlight that despite the fact that in the last 15 years many randomized controlled trials and at least 40 meta-analyzes have been published on the effectiveness and safety of IAHA for the treatment of KOA, there is still much controversy and uncertainty on this topic. [ 31 ] If we consider only some of the meta-analyzes published in the past 5 years, we will see that some of them recommend IAHA as a very effective and safe treatment, [ 24 , 32 34 ] while others contraindicate this intervention, [ 31 , 35 , 36 ] both due to its low effectiveness, as well as the lack of safety. We can explain these conflicting results for several reasons: the low quality of the meta-analyzes, [ 31 ] individual differences in the formulation of the IAHA, [ 30 ] specific clinical characteristics of the patients [ 37 ] and even the presence of conflicts of interest (declared or not) by the authors of the studies and/or financing of studies by the industry.…”
Section: Discussionmentioning
confidence: 99%
“…pharmacological management of knee OA often includes education and self-management, weight loss and strengthening, and biomechanical interventions such as knee braces [11][12][13]. Anti-inflammatories are recommended for patients with symptomatic OA of the knee to address pain; however, prolonged use of NSAIDS increases risk of gastrointestinal (GI), cardiovascular, and renal complications [14,15].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…Two other studies of the efficacy of Hyalgan ® have shown that the effects of intra-articular injection are similar to Naproxen treatment, taken continuously over a 26week period of time (17). According to the Journal of the American Academy of Orthopaedic Surgeons, Naproxen is the most effective NSAID used in the treatment of KOA with a powerful analgesic effect, but its long-term use develops characteristic NSAID's side effects (26). KOA is a surgical endwear disease.…”
Section: Osteoarthritis Treatment and Recoverymentioning
confidence: 99%